Efficacy and Safety of Exploring Deeper Sections of the Infrapapillary Area of the Duodenum by Using Sedative Esophagogastroduodenoscopy - Ming-Tse Hsu; Chi-Yi Chen; Kai-Sheng Liao; Wei-Sheng Chung (Gastroenterology Research and Practice)
Background. Using conventional esophagogastroduodenoscopy (EGD) to evaluate the infrapapillary area is not feasible. The use of sedative EGD may enable endoscopists to investigate the infrapapillary condition of the duodenum. In this study, we aimed to evaluate lesions in the infrapapillary regions by using sedative EGD. Methods. In this retrospective observational study, we used the data of patients who underwent sedative EGD examinations at a tertiary hospital in southern Taiwan. The endoscopists evaluated the esophagus, stomach, and proximal duodenum and then attempted to explore the infrapapillary portion of the duodenum as deeply as possible. We assessed the success rate for the exploration of infrapapillary areas. Furthermore, we analyzed specific clinical findings of sedative EGD examination. Results. In total, 2973 patients underwent sedative EGD between November 1, 2010, and December 31, 2011. For 2632 of these patients, it was their first sedative EGD examination. In 2511 patients (95.4%), the exploration of the infrapapillary areas was successful. In approximately 10% of the patients, specific findings were detected over the infrapapillary region, and 7 of these patients exhibited clinically significant findings (i.e., gallbladder cancer with metastasis, periampullary Vater adenoma, natural killer cell enteropathy, villous adenoma with moderate dysplasia, infrapapillary duodenal adenoma with dysplasia, duodenal perforation with tumor-like formation, and follicular lymphoma). No patient experienced minor or major adverse reactions during the sedative EGD procedure. Conclusions. The current study provided evidence that sedative EGD examination enables a safe, comfortable, and effective endoscopic examination of deeper sections of the duodenum to evaluate the papillary and infrapapillary regions.